Health financing challenges in Southeast Asian countries for universal health coverage: a systematic review - Ming Yao Lim; Hanin Farhana Kamaruzaman; Olivia Wu; Claudia Geue (BMC, 2023)
Abstract Background Universal Health Coverage (UHC) has received much attention and many countries are striving to achieve it. The Southeast Asian region, in particular, comprises many developing countries with limited resources, exacerbating challenges around attaining UHC. This paper aims to specifically explore the health financing challenges these countries face in achieving UHC via a systematic review approach and formulate recommendations that will be useful for policymakers. Methods The systematic review followed the guidelines as recommended by PRISMA. The narrative synthesis approach was used for data synthesis, followed by identifying common themes. Results The initial search returned 160 articles, and 32 articles were included after the screening process. The identified challenges in health financing towards achieving UHC in the Southeast Asian region are categorised into six main themes, namely (1) Unsustainability of revenue-raising methods, (2) Fragmented health insurance schemes, (3) Incongruity between insurance benefits and people's needs, (4) Political and legislative indifference, (5) Intractable and rapidly rising healthcare cost, (6) Morally reprehensible behaviours. Conclusions The challenges identified are diverse and therefore require a multifaceted approach. Regional collaborative efforts between countries will play an essential role in the progress towards UHC and in narrowing the inequity gap. At the national level, individual countries must work towards sustainable health financing strategies by leveraging innovative digital technologies and constantly adapting to dynamic health trends. Registration This study is registered with PROSPERO, under registration number CRD42022336624.